General design criteria for neonatal temperature monitoring sensor using "smart material" conducting polymer development: A review - Syamimi, Nor; Yahud, Shuhaida (Applied Research and Smart Technology (ARSTech), 2021)
Surface thermistors are being currently used in patient monitoring, including temperature monitoring among neonates. However, these thermistors are reported as being mechanically rigid. This review article aims to provide researchers with a guide to better design a flexible neonatal temperature monitoring sensor. A literature search was conducted to obtain available literature on temperature sensors with specific attention to designing flexible temperature sensors. The achievement of a flexible type thermistor for neonates requires a basic understanding of the thermistor. Also, the conducting polymer material being used and the rationale for their placement. The updated technology in thermistors should be made flexible for the ease of neonates during monitoring. Careful considerations for the design and conduct of flexible temperature sensor research as outlined in this review would help to enhance the quality and comparability of future research studies. Considerations for efficient neonatal temperature monitoring and protection include accuracy, sensor's size, weight, material, and sensor placement. Flexible sensors could be the alternative to conventional bulky and stiff temperature sensors.